Impact of priming on seed germination, seedling growth and gene expression in common vetch under salinity stress - Aydinoğlu, Bilal; Shabani, Akbar; Safavi, Seyed Mehdi (Cellular and Molecular Biology, 2019)
Salinity is one of the most important abiotic stress factors that is expanding its influence because of global climate change and global warming. It causes gene expression changes, a reduction in seed germination and related characteristics, and poor seedling establishment in many crop plants by creating a lower osmotic potential in the seedbed and/or toxic ion effects in germinated seeds. In recent years, seed priming has been considered a promising strategy in modern stress management to protect plants against stress conditions. This study was conducted to elucidate the effects of osmopriming with polyethylene glycol 6000 (PEG-6000) on seed germination, seedling growth and gene expression in the common vetch (Vicia sativa L.) in different saline conditions. Common vetch seeds were primed with PEG-6000 solutions having different osmotic potentials (0.00, -0.50, -0.75, -1.00, -1.25, and -1.50 MPa) for 12 hours. Control (un-primed) and primed seeds were germinated and seedlings were grown in different saline conditions (EC= zero, 4, 8 and 16 dS m-1). Furthermore, gene expression was compared in the primed seedlings in two different osmotic potentials (0.00 and -1.50 MPa) by microarray technology. Results demonstrated that germination percentage of common vetch seeds and seedling growth were diminished by high salinity. However, several priming treatments alleviated the adverse effects of high salinity on germination and early seedling growth of common vetch. The microarray showed that the expression of many genes in both stress and normal conditions was not significantly different.